Implementasi Media Crossword Puzzle Pada Pembelajaran Pendidikan Agama Islam - Isep Djuanda; Mona Rosdiana (AZKIA: Journal of Islamic Education in Asia, 2024)
The aim of this study is to find out the implementation of crossword puzzles in Islamic Religious Education Learning, to perceive the student responses on the application of crossword puzzles in learning Islamic Religious Education, and to detect the obstacle to the crossword puzzle implementation in learning Islamic Religious Education at SD Islam Al Syukro Universal Ciputat Tangerang Selatan. The study applied qualitative research to gain meaning, concepts, characteristics, and phenomena in implementing crossword puzzles in the Islamic Religious Education learning process. Data collection used in this study includes observation, interview, and documentation study, with the data analysis referred to Miles and Hubermen's theory, which covers data reduction activity, data presentation, and summary conclusion.  The study shows that: 1) the implementation of crossword puzzle media in learning Islamic Religious Education was conducted with some learning steps that consist of opening, core, and closing. 2) The student responses on implementing crossword puzzles in Islamic Religious Education learning are: a) active participation in learning process, b) enthusiasm in doing lessons, and c) independence driven by competing in filling the boxes in crossword puzzles. 3) The obstacles in implementing crossword puzzle media in learning Islamic Religious Education are: a) Teacher needs more time to design crossword puzzles; b). Implementing crossword puzzles requires reading and writing skills for students, and c) The students could only imitate other students work.